Effect of exogenous fibrolytic enzymes supplementation to improve voluntary intake, availability of nutrients and growth performance in weaned crossbred calves - ANIL; DUTTA, T K; CHATTERJEE, A; YADAV, SUSHIL KUMAR; MANDAL, D K; MOHAMMAD, A (The Indian Journal of Animal Sciences, 2023)
The present study was carried out to evaluate the effect of supplementation of exogenous fibrolytic enzymes (EFE) on voluntary feed intake, availability of different nutrients and growth performance in weaned crossbred calves. Fifteen weaned healthy female Jersey crossbred calves (weight 79.73±3.46 kg; age 234.5±11.33 days) were divided equally into three groups viz., Control (T0), Treatment-1 (T1) and Treatment-2 (T2). Growth trial was conducted on these calves for 90 days. Animals in each treatment group were fed ad lib. total mixed ration (TMR) (CP 12%, TDN 65%) individually for 90 days. Calves under control (T0) group were fed ad lib. TMR (without EFE). Calves under T1 and T2 were fed ad lib. TMR supplemented with EFE cellulase and xylanase @ 8000 and 16000 IU/kg DM of TMR and with EFE cellulase and xylanase @ 12000 and 24000 IU/kg DM of TMR, respectively. Significantly greater DMI per unit body weight (kg/100 kg BW and g/kg W0.75) was recorded in enzyme supplemented groups compared to control group; however, difference between T1 and T2 was non-significant. Addition of EFE in the TMR diet of calves increased TDN and DCP intake (g/kg W0.75) in T1 and T2 than T0 . Supplementation of EFE also enhanced TDN (%), DCP (%), DNDF (%), DE (Mcal/kg of feed) and ME (Mcal/kg of feed) value of the diets under T1 and T2 than T0. Average daily weight gain (g/d/calf) was estimated greater in T1 and T2 than T0. The feed conversion efficiency was similar among three treatments. Whereas, plasma total protein and albumin concentration increased significantly due to supplementation of EFE in the diet of calves. Therefore, it may be concluded that supplementation of exogenous fibrolytic enzymes (cellulase and xylanase @ 8000 and 16000 IU/kg TMR DM) may boost growth potential of finisher Jersey crossbred calves with enhanced intake of nutrients.